ANALYSIS OF PROJECT BASED LEARNING APPROACH IN FLIPPED CLASSROOM - Wisudawaty, Umi; Y., Y. Gatot Sutapa; Ikhsanudin, Ikhsanudin (Universitas PGRI Sumatera Barat, 2025)
This present paper describes how project-based learning as the student centred learning pedagogical approach applied in flipped classroom. The development of technology affects the teachers to apply both traditional and online teaching to support the teaching and learning process which commonly called as flipped classroom. To keep up the demands on the 21st century skill, the teacher combines the use of project-based learning as the instructional approach in flipped classroom. This paper is applied qualitative descriptive method which analyzes how the project-based learning applied in flipped classroom. The writer analyzes several research discusses how project based learning in flipped classroom effect on students‘ learning improvement. According to the analysis, it can be concluded that applying project-based learning in flipped classroom in these recent times is very fruitful and helpful to arouse students’ interest and enthusiasm in learning. It enhances students critical thinking, provides practical problems to be solved, encourages students to work collaboratively and increasing their creativity in accomplishing the project.